Attendance Logging In Webserver Using Multi Node Embedded System Connected Through Wi-Fi - Mohammed Bilal (Institute of Advanced Engineering and Science, 2012)
In the present age, we are in need of fully automated attendance logging system. The design of Remote Attendance Logging System and its control is a challenging part. RFID reader reads the RFID tag, and the details of the tag is logged in the embedded system. The Web based distributed measurement and control is slowly replacing parallel architectures due to its non-crate architecture which reduces complexities. A new kind of expandable, distributed large attendance logging system based on ARM Cortex M3 boards has been investigated and developed in this paper, whose hardware boards use 32-bit RISC processor with wifi dongle attached to its USB port, and software platform use Keil MDK-ARM for firmware and HTML for man machine interface. This system can display date and time of log in and log out of a person. The data can be displayed on web pages at different geographical locations, and at the same time can be transmitted to a Remote Data Acquisition System by using HTTP protocol. The embedded board can act as a central CPU to communicate between web servers automatically.